CONFINING PRESSURE QUANTIFICATION OF UNCONFINED COMPRESSIVE STRENGTH WITH VARIOUS SAMPLE GEOMETRY - Franklin Gunawan, Evander
In underground mining method, pillar size must be thoroughly considered depending on the weight of overburden supported. The bigger the size, it’s safety factor will be bigger but the mining recovery will be lower. Therefore a research to change the pillar with a smaller one with confining pressure is important so it will still be safe and the mining recovery will be greater. Unconfined Compression Test (UCS) and triaxial test is a common method to determine the strength of rock. Unconfined Compression Test is done to a concrete sample with 0.5, 1, 2, and 3 diameter to length ratio (D/L). Then triaxial test is done with 0.5 MPa, 1 MPa, 1.5 MPa, 2 MPa, and 2.5 MPa of confining pressure (?3) to determine how much confining pressure is needed to make 0.5 D/L sample to be as strong as the sample with bigger D/L ratio. This research concludes that sample geometry and confining pressure is crucial when determining the strength of the sample.